Substituted (сycloalkylcarbonylthioureido)aryl-(benzyl-)carboxylic(sulfonic) acids: synthesis, antimicrobial and growth-regulating activity - O. V. Kholodniak; V. V. Stavytskyi; S. I. Kovalenko (Zaporozhye State Medical University, 2021)
Acylisothiocyanates are a promising class of organic compounds that are present in the plant world and can be used in the synthesis of disubstituted thioureas and various heterocycles. These derivatives are characterized by growth-regulating, antibacterial, fungicidal, cytotoxicity, and other activities. Modification of acylisothiocyanates by fragments of substituted aminoarylcarboxylic (sulfo) acids is promising, as some of them (anthranilic, p-aminobenzoic acids) are precursors for the auxins and other natural compounds synthesis. Their combined activity is also an important aspect. Namely the simultaneous manifestation of both fungicidal and restrictive activity. Based on this, the synthesis of new substituted (cycloalkylcarbonylthioureido)aryl-(benzyl-)carboxylic (sulfonic) acids is relevant as promising regulators of plant growth with antibacterial activity. The aim of this work is to search for effective compounds with growth-regulating and antimicrobial activity among substituted (cycloalkylcarbonylthioureido)aryl-(benzyl-)carboxylic (sulfonic) acids. Materials and methods. Methods of organic synthesis, physical and physical-chemical methods of analysis of organic compounds (IR, NMR 1H-spectroscopy, chromato-mass spectrometry, elemental analysis). Antimicrobial activity studies were performed on standard strains of bacteria and fungi (S. aureus ATCC 25923, E. coli ATCC 25922, P. aeruginosa ATCC 27853 and C. albicans ATCC 885-653). The effect of synthesized compounds on growth rates was evaluated on wheat (variety Grom). Results. An "in situ" method for the synthesis of substituted (cycloalkylcarbonylthioureido)aryl-(benzyl-)carboxylic (sulfonic) acids was proposed. It was shown that the latter could be easily synthesized by the sequential interaction of cyclopropanecarbonyl chloride, ammonium isothiocyanate, and aminoaryl-(benzyl-)carboxylic, sulfanilic acids or sulfamide. Data of 1H NMR spectra showed the peculiarities of the structure of the synthesized compounds, namely the presence of singlet signals of protons of urea, thioamide and carboxyl groups, multiple signals of methine and methylene protons of cyclopropane fragment. It was found that the synthesized compounds showed moderate antimicrobial activity against S. aureus and P. aeruginosa (MIC 50 μg/ml, MBC 100 μg/ml) and significant antifungal activity against C. albicans (MIC 25-50 μg/ml, MFC 25-50 μg/ml). A number of compounds were identified as effective regulators of wheat growth and exceed the natural analogue - heteroauxin (3-indolylacetic acid) in terms of auxin-like activity. Conclusions. A one-step method for the synthesis of substituted (cyclopropanecarbonylthioureido)aryl-(benzyl-)carboxylic (sulfonic) acids was developed. The physical-chemical properties of the synthesized compounds were studied using a set of methods (IR, 1H NMR spectroscopy, chromato-mass spectrometry, elemental analysis) and the features of the structure were discussed. The synthesized compounds reveal moderate antimicrobial, high antifungal activity, and growth-promoting activity.